PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, KUALITAS AUDITOR TERHADAP OPINI GOING CONCERN PADA PERUSAHAAN INFRASTRUKTUR - wijaya, mahananta; Sri Widiawati, Hestin; Zaman, Badrus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
The phenomenon of Covid – 19 has led may companies to reveive going concern opinion, making it an interesting subject to study. The purpose of this research was to determine the effect of profitability, solvability, company size, and auditor quality on the audit opinion going concern. Type for this study is quantitative research with a descriptive research technique, using purposive sampling for data collection. The study processed 39 samples from 67companies and using SPSS 23 for processing sample. From this study we get (1) profitability aeffected audit opinion going concern (2) solvability aeffected audit opinion going concern (3) company size aeffected audit opinion going concern (4) auditor quality aeffected audit opinion going concern. This research is expected to enchance companies for give understanding of the importance of going concern and contribute to broader awareness regarding the concept of going concern.